Resilience to abrupt global catastrophic risks disrupting trade: Combining urban and near-urban agriculture in a quantified case study of a globally median-sized city - Matt Boyd; Nick Wilson (PLoS ONE, 2025)
Background Abrupt global catastrophic risks (GCRs) are not improbable and could massively disrupt global trade leading to shortages of critical commodities, such as liquid fuels, upon which industrial food production, processing and distribution depends. Previous studies have suggested urban agriculture as a resilience measure in the context of climate change and other natural hazards. Aims To estimate the contribution a radical pivot to urban agriculture could have in building resilience to GCRs and the near-urban industrial agriculture needed to supplement urban food production. Methods We determined optimum crops through mathematical optimization for food calorie and protein supply per land area for both urban and near-urban (industrial) agriculture. We calculated the land area available for food production within a temperate globally median-sized city using Google Earth image analysis of residential lots and open city spaces. We calculated the population that could be fed through urban agriculture alone, and the extra near-urban land required for cropping with industrial agriculture to feed the remaining city population, under both normal climate, and potential nuclear winter conditions. Results The optimal crops for urban agriculture were peas (normal climate), and sugar beet/spinach (nuclear winter); while those optimal for industrial near-urban production were potatoes (normal climate), and wheat/carrots (nuclear winter). Urban agriculture could feed a fifth (20%) of the population. At least 1140 hectares of near-urban cultivation could make up the shortfall. Another 110 hectares of biofuel feedstock like canola (rapeseed) could provide biodiesel to run agricultural machinery without fuel trade. Significantly more cultivated area is needed in nuclear winter scenarios due to reduced yields. Conclusion Relatively little optimized near-urban industrial agriculture, along with intensified urban agriculture could feed a median-sized city in a GCR, while minimizing fuel requirements. Governments and municipal authorities could consider land use policy that encourages development of urban agriculture and near-urban cultivation of optimal crops, along with processing and local biofuel refining capacity.